Synergistic effect of Paclitaxel and Curcumin in nano-formulations on U87 and A549 cancer cell lines - Joyceline Praveena, Sushruta S. Hakkimane, Bharath Raja Guru (Journal of Applied Pharmaceutical Science, 2022)
Prolonged use of anticancer drug like Paclitaxel increases the level of transcription factor nuclear factor kappa B (NF?B) which increases drug resistance in cancer cells. Multi-drug delivery using a combination of drugs that have different mechanisms of action has shown synergistic effects and NF?B inhibition on cancer cells, though simultaneous delivery of more than one drug formulation for cancer treatment has not been studied deeply. The low aqueous solubility of most anti-cancer drugs limits their therapeutic effect. Polymeric Nano drug delivery is a promising path that can overcome the low solubility of chemotherapeutics. The present study focuses on the development of polylactide-co-glycolic acid nanoparticles (NPs) and incorporating them with Paclitaxel/Curcumin anti-cancer drugs by single emulsion solvent evaporation method and test their synergistic effect on cancer cells. The size and surface morphology of NPs were characterized by a particle size analyzer and a scanning electron microscope. The drug loading content analyzed using reverse-phase high-performance liquid chromatography was found to be 150 and 300 µg/mg for Paclitaxel and Curcumin, respectively. In vitro release study showed a slow and sustained release of the drug from the NPs. The formulated NPs as mono or in combination form were treated against U87 and A549 cells. They showed greater cytotoxicity, increased cellular uptake, and decreased NF?B activity compared to free drugs in mono or combination form. The combination of drugs in nano-formulation showed greater cytotoxicity compared to mono drug NPs. From the results of the cytotoxicity assay, we can conclude that a combination of drugs in nanoformulation will be useful for cancer therapy.
Keywords: Polymeric nanoparticles, combination therapy, NF?B activity, PLGA, cytotoxicity